Patient-Reported Outcomes (PROs) and PRO Remission Rates in 12,262 Biologic-Naïve Patients With Psoriatic Arthritis Treated With Tumor Necrosis Factor Inhibitors in Routine Care - Ørnbjerg, Lykke M; Rugbjerg, Kathrine; Georgiadis, Stylianos; Rasmussen, Simon H; Jacobsson, Lennart; Loft, Anne G; Iannone, Florenzo; Fagerli, Karen M; Vencovsky, Jiri; Santos, Maria J; Möller, Burkhard; Pombo-Suarez, Manuel; et al. (The Journal of rheumatology, 2024)
OBJECTIVE: To evaluate patient-reported outcomes (PROs) after initiation of tumor necrosis factor inhibitor (TNFi) treatment in European real-world patients with psoriatic arthritis (PsA). Further, to investigate PRO remission rates across treatment courses, registries, disease duration, sex, and age at disease onset. METHODS: Visual analog scale or numerical rating scale scores for pain, fatigue, patient global assessment (PtGA), and the Health Assessment Questionnaire-Disability Index (HAQ-DI) from 12,262 patients with PsA initiating a TNFi in 13 registries were pooled. PRO remission rates (pain ≤ 1, fatigue ≤ 2, PtGA ≤ 2, and HAQ-DI ≤ 0.5) were calculated for patients still on the treatment. RESULTS: For the first TNFi, median pain score was reduced by approximately 50%, from 6 to 3, 3, and 2; as were fatigue scores, from 6 to 4, 4, and 3; PtGA scores, from 6 to 3, 3, and 2; and HAQ-DI scores, from 0.9 to 0.5, 0.5, and 0.4 at baseline, 6, 12, and 24 months, respectively. Six-month Lund Efficacy Index (LUNDEX)-adjusted remission rates for pain, fatigue, PtGA, and HAQ-DI scores were 24%, 31%, 36%, and 43% (first TNFi); 14%, 19%, 23%, and 29% (second TNFi); and 9%, 14%, 17%, and 20% (third TNFi), respectively. For biologic-naïve patients with disease duration < 5 years, 6-month LUNDEX-adjusted remission rates for pain, fatigue, PtGA, and HAQ-DI scores were 22%, 28%, 33%, and 42%, respectively. Corresponding rates for patients with disease duration > 10 years were 27%, 32%, 41%, and 43%, respectively. Remission rates were 33%, 40%, 45%, and 56% for men and 17%, 23%, 24%, and 32% for women, respectively. For patients aged < 45 years at diagnosis, 6-month LUNDEX-adjusted remission rate for pain was 29% vs 18% for patients ≥ 45 years. CONCLUSION: In 12,262 biologic-naïve patients with PsA, 6 months of treatment with a TNFi reduced pain by approximately 50%. Marked differences in PRO remission rates across treatment courses, registries, disease duration, sex, and age at onset of disease were observed, emphasizing the potential influence of factors other than disease activity on PROs.
Keywords: tumor necrosis factor inhibitors; psoriatická artritida; biologické přípravky; Arthritis, Psoriatic; výsledek terapie; mužské pohlaví; Pain; epidemiology; Patient Reported Outcome Measures; psoriatic arthritis; pain; ženské pohlaví; Humans; antirevmatika; hodnocení výsledků péče pacientem; inhibitory TNF; Tumor Necrosis Factor Inhibitors; Antirheumatic Agents; fatigue; Biological Products; Female; bolest; Treatment Outcome; lidé; Male